"Deus ex machina" or moving sculptures in the interior of Lutheran churches of Latvia - Spārītis, Ojārs (Landscape Architecture and Art, 2023)
The term “Deus ex machina” was used in ancient Greek and Roman theatre performances as stage machinery provided the appearance of a god or hero to unravel and resolve a hopeless situation. The present article characterizes the appearance, function, and use of moving sculptures - automatons - in Latvian Baroque church interiors. Renaissance science sparked developments in mathematics, astronomy, and mechanics that stimulated not only the invention of curiosities, but also the construction of practical mechanisms and tools. Knowledge transfer from mechanics to applied and fine arts brought moments of mystery and wonder into the fields of performing arts and the spheres of representation and liturgy. The use of automatons helped to invent new mechanisms, making the mechanical movement of “animated sculptures” an attractive public entertainment. Both written evidence and artefacts preserved in museums and churches bear witness to the social demand for the integration of theatrical elements into the formerly conservative environment, for example, the church. Drawing inspiration from the culturally linked region of former Prussia, the current paper concentrates on moving figures in the interior space of Lutheran churches in Latvia to expose the variety of fascinating objects, including organ facades and baptismal fonts.